Upaya Mengenalkan Hadits Pada Anak Usia 5-6 Tahun Melalui Metode Gerakan Tangan - Hanita Hanita; Yahdinil Firda Nadhirah; Muhiyatul Huliyah; Juhri Juhri (UIN Sultan Maulana Hasanuddin Banten, 2022)
The lack of teacher ability in using the method causes children to have difficulty remembering the hadith that has been taught. The author conducted classroom action research (CAR) introducing hadith through the hand movement method carried out at RA Ar-Rohmah Serang City on 7 children’s. CAR was carried out in 2 cycles using the Kemmis and MC Taggart models and was descriptive qualitative. The results of the CAR carried out obtained 66,07% in cycle 1 with the criteria of Developing According to Expectations (DAE) and in the second cycle it rose to 86,16% with the criteria of Very Good Development (VGD), thus the hand movement method can improve children’s ability to recognize hadith. Keywords: hand movement method; introduction to hadith; 5-6 years old References Arikunto, S. (2012). Penelitian Tindakan Kelas. Jakarta: PT Bumi Aksara. Handayani, dkk. (2015). Metode Gerakan Dalam Menghafal Hadits. Jakarta: An-Nahl. Hunainah, H., Imroatun, I., Riswanto, D., & Hayati, H. (2021). Introduction To Hijaiyah Letters Through Tilawati Method To Students Aged 5-6. Indonesian Journal of Early Childhood Education Studies, 10(2), 119–127. https://doi.org/10.15294/IJECES.V10I2.44733 Imroatun, I., Hunainah, H., Rukhiyah, Y., & Apipah, I. (2021). Perbedaan Tingkat Pengenalan Huruf Hijaiyyah melalui Metode Iqro pada Anak Kelas A Taman Kanak-Kanak. Al-Mudarris (Jurnal Ilmiah Pendidikan Islam), 4(1), 23–40. https://doi.org/10.23971/MDR.V4I1.2975 Juliana, J. (2018). Upaya Meningkatkan Daya Ingat Anak Menghafal Hadits melalui Metode Gerakan. Aṭfālunā: Journal of Islamic Early Childhood Education, 1(2), 59–63. https://doi.org/10.32505/atfaluna.v1i2.923 Kartini, Darmiyanti, A., & Riana, N. (2021). Metode mendongeng kisah nabi dalam penanaman moral anak usia dini. As-Sibyan Jurnal Pendidikan Anak Usia Dini, 7(1), 13–28. Muhiyatul Huliyah. (2016). Hakikat pendidikan anak usia dini jalur pendidikan informal. Pendidikan Guru Raudlatul Athfal, 1(1), 61–62. Nurma, N., & Maemonah, M. (2022). Hakikat Agama Dalam Pembentukan Karakter Anak Usia Dini. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 7(1), 29–40. Nuryati, N. (2017). Pengembangan Kecerdasan Spiritual Pada Anak Usia Dini Melalui Murottal Bacaan Al-Quran. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 17–26. Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60. https://doi.org/10.47200/ULUMUDDIN.V9I1.283 Refiani, D. A., Umayyah, U., & Mu’awwanah, U. (2020). Upaya Meningkatkan Kemampuan Mengenal Huruf Melalui Balok Huruf. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 4(2), 103. https://doi.org/10.32678/as-sibyan.v4i2.2442 Zakiyah, N., Nurhikma, N., & Asiyah, A. (2021). Pola Asuh Orang Tua Dalam Membentuk Karakter Disiplin Anak Usia 5-6 Tahun Pada Masa Pandemi COVID-19. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 127–138. Rusdinal dan Elizar. (2005). Pengelolaan Kelas Taman Kanak-kanak. Jakarta: Dikti. Semiawan, Conny R. (2008). Belajar dan Pembelajaran Prasekolah dan Sekolah Dasar. Jakarta: PT Indeks Sudijono, Anas. (2006). Pengantar Statistik Pendidikan. Jakarta: Rajawali. Susanto, Ahmad. (2011). Perkembangan Anak Usia Dini. Jakarta: Kencana Prenada Media Group. Wiyani, Novan Ardi. (2013). Pendidikan Agama Islam. Bandung: PT Remaja Rosdakarya. Zakiyah, N., Nurhikma, N., & Asiyah, A. (2021). Pola Asuh Orang Tua Dalam Membentuk Karakter Disiplin Anak Usia 5-6 Tahun Pada Masa Pandemi COVID-19. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 127–138.